Whose Knowledge Counts? Equity, Epistemic Justice, And Reforming Infectious Disease Research Culture - Fischer, H.; Koduah, A. (Epidemics, 2025)
Infectious disease epidemiology is shaped by engrained research cultures that privilege biomedical and quan titative knowledge systems, systematically marginalizing qualitative, contextual, and locally informed ap proaches. These hierarchies reflect deeper inequities in who leads, who participates, and whose knowledge counts—disparities often patterned along geography, gender, language, and disciplinary background. This per spectives paper examines how funding priorities, academic training, and publishing norms sustain epistemic and structural exclusion, particularly for researchers based in the Global South. Drawing on Ghana’s COVID-19 response, we show how reliance on externally developed epidemiological models mirrored broader marginali zation in research authorship, agenda-setting, and decision-making. We argue that equity-focused reforms in funding, training, and publishing—grounded in epistemic and distributive justice—are necessary to transform infectious disease research culture. A more just and inclusive research culture is not only an ethical imperative but essential to the effectiveness and legitimacy of epidemic responses.
Research Article
Keywords: Research culture; Epistemic justice; Intersectionality; Global health; Infectious disease modeling; Knowledge hierarchies; Pandemic preparedness